Transforming animal study toxicology reports into structured, harmonized data using large language models - Tatyana Y. Doktorova; Ilya Schneider Chernov; Alberto Formaggio; Xiaochen Zheng; Alvaro Serra; Preethi Latha Bhavani Mohan; Guillemette Duchateau-Nguyen; Dragomir Ivanov Draganov; Matt Hayes; Catrin Hasselgren; Vishal B. Siramshetty; Stefano Gaudio; et al. (Archives of Toxicology, 2026)

Health risks due to geogenic and anthropogenic influences on groundwater quality in Southern India's hard rock terrain - B. Preethi; T. Subramani; R. Saravanan; P. Gopinathan; Zaixing Huang; Brajesh Kumar (Journal of Geochemical Exploration, 2025)

Organic–inorganic interplay and paleoenvironmental reconstruction of Asia's largest opencast lignite mine deposits - B. Preethi; T. Subramani; T. Nathiya; Zaixing Huang (Environmental Geochemistry and Health, 2025)

Evaluation of fluoride contamination in groundwater and its non-carcinogenic health hazards in a drought-prone river basin of South India - Meera Rajan; D. Karunanidhi; T. Subramani; B. Preethi (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

A comprehensive review on human health hazards due to groundwater contamination: A global perspective - Meera Rajan; D. Karunanidhi; J. Jaya; B. Preethi; T. Subramani; P. Aravinthasamy (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Computing the Quality Characters and Acceptability of Convective Air Dried Germinated Cashew Seed Powders - P. Preethi; S. Mangalassery; S. V. R. Reddy; T. Harish; G. L. Veena; R. Pandiselvam (Applied Fruit Science, 2024)

Highly Efficacious Oil–Water Separation by Facile Stacking of the Iron Powder Waste - V. Preethi; S. T. Ramesh; R. Gandhimathi (Water, Air, & Soil Pollution, 2024)

Spatial assessment of Groundwater Quantity and Quality: A case study in parts of Chidambaram Taluk, Cuddalore District, Tamil Nadu, India - S. Venkatesan; S. Arumugam; M. Bagyaraj; T. Preethi; P. Parthasarathy (Sustainable Water Resources Management, 2021)

Role of physical oceanography parameters in ocean’s biological response with the passage of cyclone Titli in the Bay of Bengal - K Vijay Prakash; Ch S Geetha Vimala; P V Nagamani; N K Baranval; Shivashankar Manche; T Preethi Latha; I V G Bhavani; Y Umamaheswara Rao; Ch S N Phanindra; K Srinivas; K P Kumari (Journal of Earth System Science, 2021)

Assessment of Water Quality Along the Southeast Coast of India During COVID-19 Lockdown - K. Vijay Prakash; Ch. S. Geetha Vimala; T. Preethi Latha; Chiranjivi Jayaram; P. V. Nagamani; Ch. N. V. Laxmi (Frontiers in Marine Science, 2021)
The COVID-19 pandemic has affected the entire world and has had a devastating impact on both lives and livelihoods in India. The only way to defeat the rapid spread of COVID-19, is to shut down socio-economic activities and to maintain minimal human interaction with the implementation of a lockdown. Such lockdowns have manifested in a pollution curtailment in almost all spheres of the planet, including in marine pollution. Quantifying this decrease in pollution levels enables the scientific community to assess the contribution of anthropogenic (especially non-essential) activities to global/regional pollution levels. This paper aims to study the impact of the stringent lockdown period (phase 1 and 2) on coastal water quality along the Chennai coast of India, by analyzing suspended matter concentration (SPM), a key element of water quality and diffuse attenuation coefficient, K d (490), using LANDSAT-8 Operational Land Imager (OLI) data. LANDSAT-8/OLI, L1TP scenes were subjected to radiometric calibration and atmospheric correction to derive surface reflectance values from raw digital numbers using ACOLITE software and a brief insight has been given for the Dark Spectrum Fitting algorithm used in ACOLITE. SPM concentration decreased by 15.48 and 37.50% in the Chennai and Ennore ports, respectively, due to minimal vessel movement and cargo handling. The stringent lockdown led to the operation of fewer thermal plant units, thus less fly ash was emanated, resulting in a 28.05% reduction in SPM levels over Ennore creek. As industrial and commercial activities subsided, the city’s water bodies became clearer than they were just a fortnight prior to the lockdown, with a reduction of 22.26% of SPM in Adyar and 33.97% in Cooum riverine estuaries. Decrease in K d (490) showed a positive relationship with SPM and thus improved coastal water quality because of the reduction of SPM during this period. The variations in PM2.5 and PM10 concentrations were studied using National Air Quality Monitoring Programme (NAMP) data and reduced levels in particulate matter concentration (PM2.5 and PM10) for the Adyar residential area (24.38 and 28.43%) and for the Nungampakkam commercial area (36.09 and 67.18%) were observed. A significant reduction in PM2.5 concentration (45.63%) was observed in the Ennore-Manali Industrial region.

Facile green route sol–gel synthesis of nano-titania using bio-waste materials as templates - M. K. Shreya; C. Indhumathi; G. R. Rajarajeswari; Veeramuthu Ashokkumar; T. Preethi (Clean Technologies and Environmental Policy, 2021)

Satellite and In Situ Observations of a Phytoplankton Bloom from Coastal Bay of Bengal: Role in pCO2 Modulation - Rajdeep Roy; K. H. Rao; T. Preethi Latha; Vinay Kumar Dadhwal; V. V. S. S. Sarma; P. V. Nagamani; S. B. Choudhury; Seetharam Pondala (Journal of the Indian Society of Remote Sensing, 2017)

Estimation of Air-Sea CO2 Flux in the Coastal Waters of Visakhapatnam - T. Preethi Latha; K. H. Rao; V. V. S. S. Sarma; P. Seetaram; S. B. Choudhury; P. V. Nagamani; C. B. S. Dutt; V. K. Dhadwal; Sudip Manna (Journal of the Indian Society of Remote Sensing, 2015)

Setting of Cloud Albedo in the Atmospheric Correction Procedure to Generate the Ocean Colour Data Products from OCM-2 - P. V. Nagamani; T. Preethi Latha; K. H. Rao; T. Suresh; S. B. Choudhury; C. B. S. Dutt; V. K. Dadhwal (Journal of the Indian Society of Remote Sensing, 2015)

Retrieval and Validation of Chlorophyll-a Concentrations in the Coastal Waters Off Yanam and Kakinada (Godavari) Basin Along East Coast of India - T. Preethi Latha; P. V. Nagamani; K. H. Rao; S. K. Dash; S. B. Choudhury; Aziz Rehman; V. V. S. S. Sarma; M. Naveen Babu; P. Amarendra; B. Srinivasa Rao; T. D. V. Prasad (Journal of the Indian Society of Remote Sensing, 2014)